Long-term disease-free survival following comprehensive involved site radiotherapy for oligometastases - Kao, Johnny; Sahagian, Michelle; Gupta, Vani; Missios, Symeon; Sangal, Ashish (Frontiers in Oncology, 2023)
A total of 130 patients with 209 treated distant metastases were treated with a median follow-up of 36 months. The 4-year overall survival, progression-free survival, local control and distant control was 41%, 23%, 86% and 29%. Patterns of failure include 23% alive and free of disease (NED), 52% distant failure only, 9% NED but death from comorbid illness, 7% both local and distant failure, 4% NED but lost to follow-up, 4% referred to hospice before restaging, 1% local only failure, 1% alive with second primary cancer. Late grade 3+ toxicities occurred in 4% of patients, most commonly radionecrosis.Involved site radiotherapy to all areas of known disease can safely achieve durable complete remissions in patients with oligometastases treated in the real world setting. Distant failures account for the majority of treatment failures and isolated local failures are exceedingly uncommon. Oligometastases represents a promising setting to investigate novel therapeutics targeting minimal residual disease.